From Scrolling to Learning: Multimodal Arabic Vocabulary Learning through Instagram and TikTok - Mila Saadataen; Syihabuddin; Asep Sopian (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
Vocabulary acquisition is a fundamental component in mastering the Arabic language, as it forms the basis for all language skills. Technological advancements in education are driving the utilization of social media as an alternative learning tool, particularly through Instagram and TikTok within the context of Mobile-Assisted Language Learning (MALL). This study aims to describe the digitalization of Arabic vocabulary learning through these two platforms. The method used is qualitative, employing techniques of observation, document study, and triangulation. The findings show that vocabulary learning is presented multimodally through text, visuals, audio, translations, and semantic relations such as synonyms and antonyms, which is proven to enhance learners' comprehension and retention. This research introduces a novel approach by integrating the linguistic and visual aspects of social media as a model for digital vocabulary instruction. Further research is recommended to examine its impact specifically on Arabic language skills.